Volumetric proportion of grains from the Nankai subduction zone (Japan) at IODP Site 348-C0002 - Pauline Cornard; Harriet Dawson; Kevin T Pickering (PANGAEA, 2024)
Ternary diagrams are commonly used in Earth Sciences to represent numerical data as ratios of three components. For our study, ternary provenance diagrams were created in Microsoft Excel directly from the raw point-count data of sand samples from IODP sites C0002N and C0002P (presented in doi:10.1594/PANGAEA.969334). Raw point-count data were recalculated as volumetric proportions by summing up quartzose, feldspar and lithic fragment framework constituents. Other grains identified in the point counting were excluded from these calculations but were retained for later use in stratigraphic correlation.